The Reciprocal Relationship between Containers Overboard and Climate Change - Daniel, J.; Stapleton, K. A.; Stapleton, D.; Nandialath, A.; Franklin, D. (Journal of Transportation Law, Logistics, and Policy, 2021)
Not only does the flotsam and jetsam in the world’s oceans seem to be impacting the health of the world’s oceans and seas, but it appears that the warming climate and increasing CO2 emissions are impacting the global trade lanes evidenced by a greater-than-average number of lost maritime containers due to resultant rougher seas and stronger storms. We elucidate the evolution of containerized shipping and discuss the impact lost containers have on the seas and dangers to other ocean-going vessels. We also note the reciprocal effects between climate change and lost containers. The intent of our article is to shed light on these issues and we hope it sparks future research examining causal factors and their potential solutions.
Keywords: dept.mgt; peer-reviewed